The association between demography, anthropometry, serum estrogen and breast density in patients having mammography in Hospital Universiti Sains Malaysia - Haron, Juhara (2006)
Background: Breast cancer is the most common cancer in female. Report from Malaysia National Cancer Registry (NCR) 2002 showed that breast cancer account for 30.4% of all cancers followed by cervical cancer (12.4%). Many contributing factors have been identified to increase the risk of developing breast cancer. One of the factors is breast density. Dense breast tissue by mammography is associated both with epithelial proliferation and with stromal fibrosis. The relationship between these histological features and risk of breast cancer may be explained by the known actions of growth factors (hormones) that are thought to play important roles in breast development and carcinogenesis. The risk might be partly due to masking of tumors by dense tissue. Other factors such as nulliparity, late age at first birth, younger age, parity, age and duration of menopause, body mass index, hormone replacement therapy and serum estrogen may potentially affect breast cancer risk through their indirect effect on breast density. The aims of the study were to determine the characteristics of patients with mammography in Hospital Universiti Sains Malaysia and to determine the independent variables associated with breast density. Methods and Materials: This study was a cross-sectional study conducted for one year duration from May 2004 to May 2005. Data were taken from patients who came formammography in Radiology Department, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan during the study period. Data from 84 patients were collected. Results: Significant association noted between body mass index (p=0.033), parity (p=0.002) and breast density. Body mass index showed inverse relationship with breast density meaning that patients with higher body mass index had lower chance of being associated with dense breast. Results showed that for every one unit increase in body mass index, there is 0.86 times chance of association with dense breast. Inverse relationship also noted between parity and breast density. One unit increased in parity was associated with 31% reduction in chances of having dense breast (95% Cl, risk reduction range from 12% to 46% ). Serum estrogen however was not a significant independent variable for breast density. Conclusion: Body mass index and parity but not serum estrogens were significantly associated with breast parenchyma when adjusted for potential confounding factors.